Examining the Implementation of Participatory Village Autonomy: Models of Community Engagement and Application in Strengthening Inclusive Governance in Indonesia - Muhammad Mutawalli Mukhlis; Maskun, Maskun; Masum, Ahmad; Tajuddin, Muhammad Saleh; Kurniawati, Wa Ode Intan; Arowosaiye, Yusuf Ibrahim; Naswar, Naswar (Universitas Negeri Semarang, 2025)
This study rigorously examines the practical implementation of participatory village autonomy, a linchpin for inclusive governance in Indonesia. Despite formal recognition by Law No. 6 of 2014 and its 2024 amendment , significant hurdles persist, including elite domination, financial mismanagement, limited community engagement, and insufficient institutional capacity. Employing a normative legal methodology, this inquiry identifies effective models of community engagement and application for the Indonesian context. Findings affirm that village autonomy's democratization requires comprehensive legal reform, institutional strengthening, transparent administration, and active citizen involvement. Beyond mere electoral procedures, true democratization demands cultural adaptation, community empowerment, and robust accountability mechanisms to prevent elite capture. Synergistic collaboration among central, regional, and village governments is paramount for genuinely responsive local governance. Lessons from diverse precedents underscore the necessity of community-driven planning and legally mandated public participation for sustainable village development. This research concludes that empowered village autonomy can substantially foster an equitable and resilient Indonesian governance landscape, contingent upon holistic systemic reforms and diligent application of innovative engagement models.